Antibacterial Efectiveness Test of Basil Leaf Ethanol Extract (Ocinum sanctum L) Against Streptococcus pneumoniae ATCC 6301. - Khasanah, Barhoroh Nurul; Silviani, Yusianti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Basil leaves, which include flavonoids, alkaloids, saponins, tannins, and phenols, are one of the herbal plants that may be used as an antibiotic. We set out to see whether our hypothesis that an ethanol extract of basil leaves inhibited the development of Streptococcus pneumoniae ATCC 6301 bacteria would hold water. Methods from descriptive experimental research are employed in this work. As part of its Bacteriology Laboratory, the National College of Health Sciences carried out the investigation. Quantitative sampling is the method employed. Foliage picked fresh from a basil field in Klaten's Jogonalan neighborhood. Powdered basil leaves were isolated by maceration with 96% ethanol. A series of concentrations of 20%, 40%, 60%, 80%, and 100% DMSO were subsequently applied to the extract. A Kirby-Bauer assay for determining antimicrobial efficacy. Findings showed that an extract from basil leaves was antibacterial against the strain of Streptococcus pneumoniae ATCC 6301. On average, the inhibition zone diameter for basil leaf extract at 0%,40%,60%,80%, and 100% was 10.4 mm, 10.8 mm, 11.5 mm, 11.9 mm, and 13.0 mm, respectively. A 13.0 mm bland zone was generated by the maximum effective concentration of 100% in inhibiting Streptococcus pneumoniae ATCC 6301. No matter the dose, the antibacterial effects of basil leaf extract (Ocimum x africanum Lour) were able to suppress the growth of Streptococcus pneumoniae ATCC 6301. able to block 13.0 mm. C.